Strategic Communication dalam Perspektif Ilmu Komunikasi - B. Helpris Estaswara (Fakultas Ilmu Komunikasi Universitas Pancasila, 2021)
Strategic communication is a new study and beginning to develop and it is concern to many parties. However, many writings in international journals have not been identified as including communication concepts and theories. This article attempts to explain strategic communication from the perspective of communication science. The method used in this research is literature review, considering that many strategic communication thinkers have initiated their writings using literature reviews. The result, from the four definitions, found that strategic communication is built on actors, then action, interaction and negotiation, and the last is meaning. Actors in strategic communication are not only single actors, but multiple actors. With multiple actors, strategic communication will be more important and relevant. Whereas action, interaction and negotiation, in strategic communication, it is not only action, but interaction and negotiation are the discussion. Finally, meaning in strategic communication is a process from multiple actors, where they simultaneously carry out actions, interactions and negotiations.